Laparoscopic Surgery for Ovarian Cyst Infection with Avoidance of Ureteral Injury and Uterine Perforation following Intrauterine Insemination after Abdominal Modified Radical Trachelectomy - Moito Iijima; Shigenori Hayashi; Yusuke Kobayashi; Kosuke Tsuji; Eiichiro Tominaga; Kouji Banno; Daisuke Aoki (Hindawi Limited, 2019)
Pelvic inflammatory disease (PID) sometimes develops after intrauterine insemination (IUI). We herein present a case of PID which developed after IUI performed after abdominal modified radical trachelectomy (AmRT) and was treated with laparoscopic surgery. To our knowledge, this is the first case report of laparoscopic surgery for PID that occurred after AmRT in Japan. A 39-year-old woman who was diagnosed with cervical cancer stage IA1 with lymphovascular invasion underwent AmRT and pelvic lymphadenectomy. At 3 years and 6 months after the surgery, she had fever and pain in her left lower abdomen 10 days after IUI. She was diagnosed with PID with left ovarian cyst infection and underwent laparoscopic left ovarian cystectomy. Before surgery, bilateral ureteral catheters were inserted because of possible difficulty identifying the ureters. During surgery, severe adhesion was seen in the pelvic cavity. By moving the catheters manually back and forth from outside the body, we were able to identify the ureters visually. A uterine manipulator was inserted during surgery, rather than before surgery, to avoid the risk of uterine perforation. Laparoscopic surgery with ureteral catheters and a uterine manipulator can be applied safely for such cases after AmRT even when severe intraperitoneal adhesion is present.